2023
DOI: 10.1021/acscatal.3c03210
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Photoelectrochemical Reduction on TiB2 Surface Plasmon Coupling Allows Us to Reach Enhanced Efficiency of Ammonia Production

Abstract: Ammonia is one of the most widely produced chemicals worldwide, which is consumed in the fertilizer industry and is also considered an interesting alternative in energy storage. However, common ammonia production is energy-demanding and leads to high CO2 emissions. Thus, the development of alternative ammonia production methods based on available raw materials (air, for example) and renewable energy sources is highly demanding. In this work, we demonstrated the utilization of TiB2 nanostructures sandwiched bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…This ability is attributed to the synergistic effect between transition metal and boron atoms. While the transition metal atoms promote N 2 adsorption by accepting a lone pair of electrons from 2s–2p orbitals of N 2 to its d-orbitals, the boron atoms facilitate N 2 activation by stabilizing the intermediate species through charge modulation. ,,,,,,, Second, these nanosheets are expected to have a large number of active sites, owing to their highly reactive edges. In addition, the vacancies introduced in our nanosheets due to exfoliation also create additional active sites on the basal plane (considered inactive in many van der Waals materials). Finally, these nanosheets would provide more flexibility to accommodate reaction intermediates than their bulk counterparts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This ability is attributed to the synergistic effect between transition metal and boron atoms. While the transition metal atoms promote N 2 adsorption by accepting a lone pair of electrons from 2s–2p orbitals of N 2 to its d-orbitals, the boron atoms facilitate N 2 activation by stabilizing the intermediate species through charge modulation. ,,,,,,, Second, these nanosheets are expected to have a large number of active sites, owing to their highly reactive edges. In addition, the vacancies introduced in our nanosheets due to exfoliation also create additional active sites on the basal plane (considered inactive in many van der Waals materials). Finally, these nanosheets would provide more flexibility to accommodate reaction intermediates than their bulk counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have studied the combined effect of transition metal and boron atoms on NRR mechanisms. , Recently, AlB 2 -type diborides such as bulk MoB 2 , FeB 2 , and CoB 2 were used for nitrogen and nitrate conversion, showing promising results. , In 2021, researchers experimentally showed the potential of TiB 2 thin films where they used them as a catalyst for NRR . However, all these borides have been used in their bulk forms (size in micrometers), which limits the charge transfer and the surface area available for catalysis. Alternatively, nanosheets of metal diborides provide a much larger surface area and are thus expected to have superior catalytic properties for NRR. , This was showcased in a recent study by Zabelina et al, where they performed photoelectrochemical NRR using plasmonic properties of gold in the gold-TiB 2 nanocomposite . We recently demonstrated that exfoliated TiB 2 nanosheets having defects can chemisorb nitrogen with minimal energy requirements due to Ti–B synergy. , This unique property of TiB 2 nanosheets to chemisorb N 2 motivated us to test their candidacy for NRR. ,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome these limitations, several strategies are being explored. These include the development of heterostructures, [77][78][79][80][81] which enhances light absorption and facilitates charge-transfer dynamics, heteroatom doping, [82,83,92] which modifies electronic properties and tailors catalytic sites, and surface modifications, [84,85] which increases active sites and improves interaction with N 2 molecules. Each of these approaches aims to optimize the PEC performance and advance the field toward a more efficient and environmentally friendly NH 3 production process.…”
Section: N 2 Reductionmentioning
confidence: 99%
“…12–14 However, N 2 is poorly soluble in aqueous electrolytes and has a high NN bond energy (941.69 kJ mol −1 ), which requires a large amount of energy to break. 15–17 In contrast, NO 3 − is a pollutant in water above a concentration of 10 mg L −1 . Overall, electrochemical coupling of the lower formation energy NO 3 − contaminant with CO 2 to prepare urea is a win–win approach for environmental management and organic small molecule production.…”
Section: Introductionmentioning
confidence: 99%